Pulp tissue regeneration in the treatment of immature premolars accompanied by infection: A case report - Gabriella Djuanda, Anastasia; Dianti, Eska; Auzan Fepiosandi, Radixtio; Lazuardi Ramadhan, Daniyal; Agustin Wahjuningrum, Dian; Setyabudi (Conservative Dentistry Journal, 2022)
Background: Young permanent teeth are one of the challenges in performing endodontic treatment. Revascularization is a good yet simple treatment option for pulp tissue regeneration to stimulate periapical lesion healing, continue root growth and restore pulp tissue function. Purpose: This case report describes management of pulp tissue regeneration in teeth with infection. Case: Female, 16 years old, came complaining of pain in the left lower back tooth accompanied by recurrent swelling. Radiograph showed an open apex with apical lesion on tooth 35. The diagnosis was pulpal necrosis accompanied by a chronic apical abscess. Case management: The treatment plan was revascularization and direct composite restoration. After accessing the cavity, the teeth were prepared, irrigated, and medicated with TAP, which was repeated for 2 visits. On the next visit, after the root canal was cleaned, over instrumentation was performed for bleeding and Collaplug was placed over the blood clot, covered with MTA, and composite resin for coronal sealing. Follow up was carried out for up to 9 months and was asymptomatic. Radiographs show healing of the lesion accompanied by closure of the root canal. Conclusion: Regenerative endodontics has been shown the successful in stimulating root canal closure to treat immature teeth